Dampak Transformasi Digital dan Otomatisasi terhadap Praktik Akuntansi: Studi Pada Bursa Efek Indonesia - Laoli, Victorinus (Jurnal Akuntansi AKTIVA, 2024)
Abstract. This study aims to explore the impact of digital transformation and automation on accounting practices in companies listed on the Indonesia Stock Exchange. In the current digital era, technology plays a crucial role in enhancing the efficiency and accuracy of financial reporting. Through a literature review, this research identifies the benefits gained from technology adoption as well as the challenges faced by companies. The findings indicate that while digital transformation offers improvements in efficiency and decision-making quality, issues such as system integration and employee skills remain significant obstacles to overcome. This research provides valuable insights for companies in planning and implementing digital transformation in their accounting practices. Keyword : Digital Transformation, Automation, Efficiency, Employee Skills